2019
DOI: 10.3390/diagnostics9040158
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Muscle Stiffness in Infants with Congenital Muscular Torticollis

Abstract: Congenital muscular torticollis (CMT) results from unilateral shortening of the sternocleidomastoid (SCM) muscle, usually associated with a fibrotic mass. Although CMT may resolve with physical therapy, some cases persist, resulting in long-term musculoskeletal problems. It is therefore helpful to be able to monitor and predict the outcomes of physical therapy. Shear-wave velocity (SWV) determined by acoustic radiation force impulse (ARFI) elastography can provide a quantitative measure of muscle stiffness. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…The effect of SCM, in these torticollis cases, was similar to other studies in the literature. 10,11,14 In this study, muscle echogenicity was found to be isoechoic in most of the recruited patients. Isoechoic patient cases were followed by hyperechoic example.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The effect of SCM, in these torticollis cases, was similar to other studies in the literature. 10,11,14 In this study, muscle echogenicity was found to be isoechoic in most of the recruited patients. Isoechoic patient cases were followed by hyperechoic example.…”
Section: Discussionmentioning
confidence: 51%
“…The specific etiology of CMT is uncertain. 3,11 Venous compression of the neck, fibrous hemorrhages in the peripartum period, and primary myopathy during the intrauterine period may have pathologic linkage. 12 Histologic examination of surgically resected materials has revealed atrophy and fibrosis in cases developed due to intrauterine venous compression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CMT is a muscle-derived condition, the insufficient number of muscle SWE studies addressed the SCM stiffness indicates a large gap in the literature. It was reported that the stiffness of the affected SCM was positively correlated with the degree of PROM deficit of neck rotation in the affected side [39][40][41] and affected SCM stiffness was significantly higher than that of the unaffected SCM and than that in the control group [39]. Hwang et al also reported that SCM stiffness decreased significantly after 3 months of physiotherapy [41].…”
Section: Congenital Muscular Torticollismentioning
confidence: 96%
“…It was reported that there was a positive correlation between the severity of scoliosis and pelvic obliquity in patients with adolescent idiopathic scoliosis. There were some children seen with both secondary scoliosis and pelvic asymmetry among the children with a history of CMT [ 19 ].…”
Section: Introductionmentioning
confidence: 99%